A Case Report of Intraparenchymal Neurocysticercosis in a Postpartum Female in Saudi Arabia - Alshamrani, Foziah Jabbar (Saudi J Med Med Sci, 2020)
Neurocysticercosis is a neurologic disease caused by infection with larvae of Taenia solium. It is most commonly transmitted by consumption of pork, water contaminated with T. solium or poor hygiene habits. As only few cases of neurocysticercosis have been documented in Saudi Arabia, the authors report a case of neurocysticercosis in a young Indian female residing in Saudi Arabia who presented with generalized tonic–clonic seizures 6 days after a normal vaginal delivery. Her physical and laboratory investigations as well as chest X-ray and electroencephalogram were all normal. Computed tomography of the head revealed multiple calcified nodular lesions, and magnetic resonance imaging showed ring-enhancing lesion in the left frontoparietal area. Serum enzyme-linked immunosorbent assay (qualitative) was positive for immunoglobulin G antibodies for cysticercosis. A diagnosis of neurocysticercosis was made, and the patient was treated with dexamethasone and levetiracetam for 4 days before discharge. At the 3-month follow-up, the patient's condition had significantly improved, and her seizures had not recurred. This report recommends considering neurocysticercosis as a differential diagnosis in patients presenting with new-onset seizures, even if the symptoms do not initially indicate neurocysticercosis or if the patient resides in an area where the disease is rare.